1968
DOI: 10.1002/pssb.19680290114
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Lattice Absorption of Silicon and Germanium

Abstract: The two-phonon absorption bands of silicon and germanium are calculated taking into account the second-order dipole moment up to second-nearest neighbours. The agreement between the calculated and measured bands shows that the shell model used in our calculations gives quite good phonon dispersion curves. The detailed analysis of the remaining deviations between measured and calculated frequencies indicates that in some points of the Brillouin zone the shell model should be corrected.Die Zweiphononen-Absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The vibrational energy of B-CO, obtained in our calculation, is at resonance with the Si-bulk phonon continuum, whereas that of T-CO is off the resonance [39]. Therefore, the vibrational energy of B-CO is strongly coupled to the bulk phonons, and decays very rapidly.…”
Section: Discussionmentioning
confidence: 58%
“…The vibrational energy of B-CO, obtained in our calculation, is at resonance with the Si-bulk phonon continuum, whereas that of T-CO is off the resonance [39]. Therefore, the vibrational energy of B-CO is strongly coupled to the bulk phonons, and decays very rapidly.…”
Section: Discussionmentioning
confidence: 58%
“…Several papers present critical-point analysis for twophonon features in Si and Ge: the works by Johnson, 37 Johnson and Loudon, 42 Balkanski and Nusimovici, 43 Fray et al, 39 Kress, et al, 44 and Ikezawa and Ishigame, 36 indicated by acronyms J, JL, BN, FJQW, KBW, and II in Tables II and III that are discussed below. Johnson's paper contains a fairly thorough review of aspects of critical-point analysis in earlier work.…”
Section: ͑23͒mentioning
confidence: 99%
“…The functions F,,,(w), independent of potential parameters, are defined and calculated in a manner analogous to that of [19] ; they are determined by the crystal structure and the eigenvectors and eigenvalues of the harmonic model. K is a constant being built of the eigenvectors and the eigenfrequency of the dispersion phonon.…”
Section: Anharmonic Effects In the Infrared Absorption Of Csbrmentioning
confidence: 99%